(untitled) (Al-Academy, 2020)
Color in the fantasy child theater represents a psychological and sematic symbol in conveying the connotations and clarifying meanings being an exciting and clarifying means. The researcher felt the necessity of shedding light on the color semiotics in the theater shows presented for children which are characterized by fantasy atmospheres and the ability to employ the color semiotics that goes along with the nature of the Iraqi theater shows through the following question: What is the extent of the representation of the color significance of the mark shown in the fantasy theatrical show presented to the Iraqi child? The aim of the research is: Exposing the color utilization and its semiotic significance in the fantasy Iraqi child theater. The research is limited to the color semiotics of the fantasy theatrical shows presented for children in Iraq within the period (2008-2018). The results of the research showed the dependence of the specialist in the theatrical fantasy work on the color signs of different kinds (iconic, indicative and symbolic) and taking care of the psychological side of the recipient and what the color means from the psychological point of view. The proper use of the colors in lighting, décor and fashion has emerged in a convincingly and impressively way for the child